The Influence Of Accounting Knowledge, Self Efficacy And Interpersonal Individuals On Students' Career Interest As Public Accountants - Prastyatini, Sri Lestari Yuli; Kaleka, Frischa Aprilia (Kontigensi : Jurnal Ilmiah Manajemen, 2025)
To empirically examine the effect of accounting knowledge, self-efficacy and individual interpersonal on students' career interest as public accountants. This research is a type of quantitative research and the data used in this research is primary data. Primary data was obtained through distributing questionnaires distributed via WhatsApp to undergraduate accounting students at the Faculty of Economics, University of Yogyakarta.. Accounting knowledge, Self-efficacy and Interpersonal individuals have a positive effect on Student Career Interest as a Public Accountant. This research provides a dual contribution. Practically, the results of the study can help students, universities, the business world, and policy makers in understanding the factors that influence interest in becoming a public accountant, so that they can take more appropriate steps. Theoretically, this research enriches our understanding of career interest and paves the way for further research in the field of accounting. This study only relies on one data source, namely a questionnaire, so that the information obtained is limited to the opinions of respondents without being complemented by additional data through interviews. And this research is less able to be generalised only focusing on the faculty of economics in the Special Region of Yogyakarta.